2009
DOI: 10.1007/s00432-009-0628-y
|View full text |Cite
|
Sign up to set email alerts
|

A predicted functional single-nucleotide polymorphism of bone morphogenetic protein-4 gene affects mRNA expression and shows a significant association with cutaneous melanoma in Southern Italian population

Abstract: This study evidences the relevance of using bioinformatics tools in searching for cancer-associated gene polymorphisms and suggests that the predicted functional SNP 6007 C/T affects BMP4 gene expression and the risk to development of CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
2
23
0
5
Order By: Relevance
“…Melanoma risk is determined by a large number of variables. We have recently demonstrated that a predict functional SNP of BMP4 could influence the susceptibility to CM 26 and other genetic associations with the risk of CM have been found. 27 The association between MDM2 SNP309 and tumor risk has been evaluated in diverse populations including diverse tumor types (lung, breast, colorectal, bladder, ovarian and so on).…”
Section: Discussionmentioning
confidence: 96%
“…Melanoma risk is determined by a large number of variables. We have recently demonstrated that a predict functional SNP of BMP4 could influence the susceptibility to CM 26 and other genetic associations with the risk of CM have been found. 27 The association between MDM2 SNP309 and tumor risk has been evaluated in diverse populations including diverse tumor types (lung, breast, colorectal, bladder, ovarian and so on).…”
Section: Discussionmentioning
confidence: 96%
“…Non-synonymous SNPs are always evaluated for their effect on protein stability and/or function. Some investigations have reported the impact on the transcriptional process and mRNA stability as a result of non-synonymous SNPs [68], [69]. To determine whether this SNP may modulate the expression of this gene and influence the structure or function of the related protein, real-time PCR analysis and functional prediction of non-synonymous SNP were performed.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed more negative predicted free energy for Haplotype 2 compared with Haplotype 1, which appeared to predominantly result from effects of the rs3814058 t>c SNP. More negative free energy should lead to a more stable structure with less mRNA degradation and higher levels of Haplotype 2 mRNA compared with Haplotype 1 mRNA, as has been previously reported for SNPs in several other genes (Capasso et al 2009; Wang et al 2005; Wang and Sadee 2006). In support of this contention we observed higher PXR -3′UTR mRNA levels in those individuals that carried the rs3814058 SNP (including Haplotype 2).…”
Section: Discussionmentioning
confidence: 57%